Strength Development of Fly Ash-Perlite Based Geopolymer Mortar Using Recycled Waste Glass as Fine Aggregate - Photisan, Methawee Sriwattanapong; Sangphong, Onanong (Naresuan University Journal: Science and Technology (NUJST), 2022)
In this paper, the synthesis of geopolymer mortars using fly ash and perlite with mixing recycled waste glass as a partial fine aggregate replacement was studied. Perlite was used to replace fly ash at weight percentages of 0 to 10, 20, 30, and 40. Waste glass was crushed with the size close to sand. Sand was replaced by waste glass at 20% by weight. Sodium silicate and 10 molar sodium hydroxide solutions were prepared as alkali activator. The workability, strength development, and fire resistance of geopolymer mortars were investigated. The results indicate that the flow and compressive strength of mortars decreased with an increase in perlite content. The strengths of fly ash-perlite geopolymer mortars at 28 days were in the range of 44 to 51 MPa, which is suitable for some engineering applications. The high strength for refractory applications was 95 MPa (70FA30PL), which increased as the sintering temperature increased. Keywords: geopolymer, fly ash, perlite, waste glass, compressive strength, fire resistance